Rising temperatures trigger warming-wetting conditions in the East River Basin, China - Chang Lu; Da Liu; Qiang Zhang; Chong-Yu Xu; Jianfeng Li; Gang Wang; Xihui Gu; Deliang Sun; Vijay P. Singh (Journal of Hydrology: Regional Studies)
Study region: The East River Basin (ERB) is located at the junction of the Western Pacific Ocean, the South China Sea, and Eurasia. Study focus: In 2011–2012, the ERB suffered severe droughts in all four seasons, so the wetting and/or drying tendency of the ERB had aroused widespread concern. Based on the ERA5 reanalysis and CMIP6 multi-model datasets, we used a Lagrangian trajectory model to unravel precipitation, temperature, and evaporation changes during the historical period 1981–2023 and predict wetting and/or drying tendencies (measured by precipitation minus evaporation, PME) during the future period 2024–2099. New hydrological insight for the region: During the historical period, average annual precipitation decreased (-10.3 mm/a), evapotranspiration increased slightly (0.87 mm/a), and air temperature increased significantly (0.29°C/10a). We found that precipitation decreased over the northern and central ERB and evapotranspiration increased over the west to 115°E, while temperature increased over the eastern ERB, resulting in a warmer and drier state over the entire ERB. External water vapor input is the prime driver of precipitation change (accounting for 79 % of the total), mainly from the North Pacific Ocean (31 %) and the Indian Ocean (26 %). The net water vapor fluxes declined in the late 20th century and peaked in 2006, and then decreased rapidly until 2023, wherein internal water cycle contributed to 21 % of precipitation change. Under the 1.5°C warming scenario, ERB will be in a warming-drying state, while under higher warming levels (2°C, 3°C, 4°C warming scenarios), ERB will be in a warming-wetting tendency. These findings can provide an important reference for basin-scale water resources management and mitigation of water issues in the context of climate warming.